Factors Factors Affecting the Form of Teacher Recruitment in Schools - Masayuki Nugroho; Bachtiar Syaiful Bachri; Umi Anugerah Izzati; Amrozi Khamidi; Nunuk Hariyati (Jurnal Indonesia Sosial Teknologi, 2024)
The purpose of this study is to find out the factors that affect teacher recruitment in schools. This research method uses the Systematic Literature Review (SLR) method. In the future, small and medium-sized companies face the challenge of retaining their best human resources to keep working for the company. Aligning individual values with work, organisation, and group is the best way to achieve goals through creative changes in employee behaviour. They found that misinterpretations of cultural roles, stigma, fear and prejudice, low status of educators in the preschool sector, and lack of male recruitment policies influenced male recruitment into the preschool sector. This study concludes that the factors that affect teacher recruitment in schools are education, experience, gender, salary, facilities, working conditions, job satisfaction, career advancement opportunities, location (urban and rural), people organisation, personal motivation, organisational practices, compatibility between personal characteristics and job needs, values, social cognitive career, self-decision, career construction, living space, commitment, teacher competence, social cognitive, sustainable professional development. The recruitment stages at the school are committee formation, socialisation, registration, and selection process, which includes written exams, interviews, and microteaching. After the selection process is complete, qualified teachers are announced. Hiring can run smoothly if supported by facilities, team collaboration, and human resources.